Contextual Layers in the Establishment of Research Niche in Doctoral Thesis Introductions by Malaysian Writers - Zainuddin, Siti Zaidah; Shaari, A.H. (Universiti Kebangsaan Malaysia Press, 2017)
One of the key moves in thesis introductions in terms of Swales’s CARS is Move 2: Establishing the Niche. It is where researchers provide the justifications of the study after introducing the general area of the research. However, research findings of prior work have focused on thesis introductions which relates to how texts are constructed and organised in systematic ways in terms of Swales’s (1990) CARS moves and steps, and how these two organisational elements assist in achieving the overall purpose of the genre. These move analysis studies of Introductions do not examine and explain why each move and step are written the way they are through the lens of various contextual layers. The current study views genre through the Contrastive Rhetoric (CR) lens in looking at context as multilayered. The study examines how different levels of context influence how eight ESL Malaysian writers establish their research niche. Adopting the functional-semantic approach to analysis, it can be concluded that apart from the multi-layered discourse community of their academic setting, the socio-cultural and socio-political contexts have a significant effect on the establishments of the writers’ research niche.